Development of Ag‐dendrites @Cu nanostructure for removal of selenium (IV) from aqueous solution. (26th April 2022) - El‐Wakeel, Shaimaa T.; Abdel‐Karim, Ahmed; Ismail, Sameh H.; Mohamed, Gehad G.
Abstract: Removal of selenite (Se (IV)) from wastewater is vital due to its more toxic and mobile properties. In this study, a novel dendritic silver‐dendrites@ copper with hierarchical side‐branches were synthesized through a two‐pot rapid, facile, and green precipitation route. Characterization of the dendrites by transmission electron microscope (TEM), scanning electron microscope (SEM), dynamic light scattering (DLS), and X‐ray diffraction spectroscopy (XRD) confirmed the proper preparation of dendritic AgCu nanostructure. Significantly, the Ag@Cu nanostructure has high specific surface area (150 m 2 /g) and excellent adsorption activity toward selenite. The adsorption rate of Se (IV) on the dendritic AgCu reaches 94% within 60 min under normal adsorption procedures. Both adsorption kinetics and isotherms have been described well by the pesudo‐second order model and Langmuir model, respectively. The noticeable high adsorption capabilities can mainly accredit to the effect of the hierarchical side‐branched structure. Therefore, the dendritic AgCu nanostructure has a room of treating heavy metals‐contaminated industrial wastewater streams. Practitioner Points: Silver‐dendrites@ copper with hierarchical side‐branches were synthesized through a rapid and green precipitation route using copper nanoparticles. The prepared nanostructure was applied for Se (IV) adsorption at varying operational conditions (contact time, pH, and dose). High adsorption capacity for Se (IV) up to 173.1 mg/g was achieved using the prepared nanoparticles applying Langmuir isotherm model. Abstract : Removal of selenite (Se(IV)) from wastewater is vital due to its more toxic and mobile properties. In this study, a novel dendritic silver‐dendrites@ copper with hierarchical side‐branches were synthesized through a two‐pot rapid, facile, and green precipitation route. The adsorption rate of Se(IV) on the dendritic AgCu reaches 94% within 60 min under normal adsorption procedures. Both adsorption kinetics and isotherms have been described well by the pesudo‐second order model and Langmuir model, respectively.